Markets, equality and democratic education: Confronting the neoliberal and libertarian reconceptualisations of education - Youl-Kwan Sung (Perspectives in Education, 2010)
The global emergence of market liberalism marks an effort to decouple the link between citizenship and the welfare state and to rearticulate people’s identity as homo economicus, as independent citizens having the right to property and the freedom to choose in the marketplace. Confronting this phenomenon, this paper reviews neoliberal and libertarian understandings of educational equality and democratic education and interrogates the rationale for the justification of markets in education. In the process, I criticise the notion of possessive individualism as a principle of democratic education on the grounds that such a notion explains human action only at the individual level, as a matter of free will, and not as a part of the cultural and political struggle for nondiscrimination. I also provide reasons why the claim to equal respect and recognition needs to be given more importance in education and argue for the social responsibility to secure not only students’ educational opportunities, but also their opportunity to reflectively consider what counts as equal value.